Analysis of Speech Functions in the Lyrics of "Free Palestine" by Maher Zain - Lubis, Firda Fadhilah Muzanni; Karim, Abdul; Nabujing, Nurul Hidayah; Wardani, Aisyah Risti; Rangkuti, Linda Astuti; Fransiska, Widia (EXCELLENCE: Journal of English and English Education, 2024)
This research examines the speech functions present in the lyrics of Maher Zain's song "Free Palestine," which was recently released in June 2024. The song was selected because its lyrics serve not only as entertainment but also as a means to convey important messages, raise awareness, and foster empathy for current humanitarian issues. The primary objective of this study is to investigate how speech functions are realized in the lyrics of "Free Palestine" through discourse analysis. The research employs a qualitative approach. The data were analyzed focusing on speech functions. The data analysis process involved several steps, namely: initially identifying the lyrics, segmenting the lyrics into clauses, analyzing the clauses in terms of its function, determining the Mood types based on their grammatical structures (Declarative, Interrogative, Imperative, and Exclamative), and identifying speech functions, and drawing conclusions. The results revealed there were three types of Mood: Declarative, Interrogative, and Imperative. Declarative statement was predominant in the song, comprising 73.68% of the total analyzed clauses.